As Políticas Sociais na América Latina: fundamentos e contradições - Santos, Eduarda Isis Vicente dos (2018)
This dissertation deals with the configurations of Social Policies and their relation with the inequality and / or poverty of Latin America, specifically with the societal changes in the configuration of the State and the economic scenario in the face of the neoliberal offensive. In order to achieve this research, we resorted to bibliographical and documentary research, using classic and contemporary authors, in order to critique the a-historical view of the constituent elements of Latin American history. The historical foundations of the formation of this continent and the responses of the State through social policies are rescued. It seeks to understand the challenges faced in the contemporaneity by the working class, through superexploration. The contemporary debate has brought new forms of exploitation for the worker with the crisis of capital: high unemployment and the control of social reproduction by social policies, more specifically, by social programs. The inclusion of social programs to fight extreme poverty, with a reversal of the meaning of "citizenship", can be seen, since social programs are excluded from social policies that should be universal in this model of society. This study locates the object of research in the historical soil that engenders it, highlighting its contradictions and limits, specifically in Latin America. Knowing the historical process of this continent that triggered strategies of exploitation of the worker of more intense form, is necessary for the elaboration of ways of strengthening. The effects generated by the strategies in order to maintain the reproduction of capital through social policies are inserted in a structural dynamic, in which dependence and overexploitation make impossible the guarantee of the minimum of social protection to the great part of the working class.